Pengaruh Jumlah Ayam Per Induk Buatan Terhadap Performan Ayam Petelur Strain Isa Brown Periode Starter - D Risnajati (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2014)
This studyaimedtodetermine the extent ofthe influence ofthe number of chickensper litteronthe performanceof laying hensstrain IsaBrown onstarter periodandhow manychickens thatproduce thebestperformance ofbrooderwitha diameter of4meters.The research methodusedexperiment was acompletely randomized design(CRD) with3treatments, namelythe number of chickens500 heads(K1), 750heads(K2), and 1000heads (K3) perbrooderof each treatment was 9 replication. Parameters observed that feed consumption, body weight gain, feed conversion, water consumption, and mortality. Effect of treatment performed by analysis of variance and if the analysis showed a significant effect followed by Duncan's multiple range test. Increasing the number of chickens per flock artificial influenced of reducing body weight gain and increasing water intake, but had no effect on feed intake, feed conversion, and mortality. Good performance of chickens obtained from the amount of 750 per brooder chicken (K2) was shown with body weight gain approaching recommendation Guide Isa Brown (2005).Keywords: brooder, the performance of laying hens, the starter period